2012
DOI: 10.22458/urj.v4i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Variación morfométrica y geográfica entre poblaciones de <em>Hypsiboas cordobae</em> (Anura: Hylidae) en Argentina

Abstract: Las diferencias fenotípicas intraespecíficas entre poblaciones separadasgeográficamente es común entre los anfibios anuros. En el presentetrabajo se realiza una caracterización morfométrica de Hypsiboascordobae, con el objetivo de estudiar la variación geográfica a lo largode la distribución de la especie. Se midieron 15 variables un totalde 86 individuos, pertenecientes a seis localidades de las provinciasde Córdoba y San Luís. Se observó dimorfismo sexual en diez de lasvariables. El análisis comparativo most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In the results presented by Baraquet et al (2012), individuals from Las Guindas (930 m elevation) showed lowest values in all morphometric variables and differing significantly from the other populations. However, in this paper age was not used as covariate.…”
Section: Discusionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the results presented by Baraquet et al (2012), individuals from Las Guindas (930 m elevation) showed lowest values in all morphometric variables and differing significantly from the other populations. However, in this paper age was not used as covariate.…”
Section: Discusionmentioning
confidence: 75%
“…Boana cordobae (Barrio, 1965), endemic to Argentina, is one of the most common anuran species breeding in rivers and streams from Córdoba and San Luis provinces (Barrio, 1965;Cei, 1980;Baraquet, Salas, & Martino, 2013). Although age, growth, sexual size dimorphism (Otero et al, 2017a) and geographic variations in morphometric variables (Baraquet, Grenat, Salas, & Martino, 2012) have reported in recent years, there is no information about relationships between morphometric variables and age of the individuals along a altitudinal range. Since in that different altitudes represent different environmental conditions, we hypothesized that life-history traits among populations will be different, with values of age and morphometric variables greater at high-altitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation